1996
DOI: 10.1046/j.1365-3024.1996.d01-66.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the induction of apoptosis the mechanism of the protective effects of TNFα in helminth infection?

Abstract: Tumour necrosis factor alpha has been implicated in protective immune responses to a number of parasitic helminths. However, the final effector mechanisms resulting in death or expulsion of the parasite are unclear. Here we suggest that, by employing phylogenetically conserved mechanisms, the mammalian immune system is able to interfere with helminth development directly and that the protective effects of TNF alpha in helminth infections may operate via the induction of parasite apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As shown in Figure 3, with the increasing concentrations of LCL161, the morphological changes indicative of apoptosis in PSCs was more obvious, the apoptotic rate in PSCs was gradually up-regulated, and the transcription levels of both IAP and BIRP genes were also significantly downregulated. Garside (Garside et al, 2010) reported that in helminth infections, caspase, as a TNFα-related factor, can induce the apoptosis in parasites through external signals to hinder their growth. Intriguingly, results of present study also demonstrated that, LCL161-mediated degradation/disruption of the IAPs in caspase-IAPs complexes might have triggered the activity of caspase and result the apoptosis in PSCs, and further studies will be carried out to evaluate the mechanism of Eg-IAPs inhibiting caspase activity in E. granulosus.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3, with the increasing concentrations of LCL161, the morphological changes indicative of apoptosis in PSCs was more obvious, the apoptotic rate in PSCs was gradually up-regulated, and the transcription levels of both IAP and BIRP genes were also significantly downregulated. Garside (Garside et al, 2010) reported that in helminth infections, caspase, as a TNFα-related factor, can induce the apoptosis in parasites through external signals to hinder their growth. Intriguingly, results of present study also demonstrated that, LCL161-mediated degradation/disruption of the IAPs in caspase-IAPs complexes might have triggered the activity of caspase and result the apoptosis in PSCs, and further studies will be carried out to evaluate the mechanism of Eg-IAPs inhibiting caspase activity in E. granulosus.…”
Section: Discussionmentioning
confidence: 99%
“…They can affect T cells and alter their capacity for proliferation or apoptosis [ 65 ], which affects the balance of the Th1/Th2/Treg response. In addition, some helminths induce apoptosis (i.e., the so-called programmed death) of various immune effector cell populations [ 66 ]. Some helminths affect the level of antibody production by switching the expression of genes encoding IgE antibodies to IgG4 antibodies.…”
Section: Molecular Mechanisms and Immune Response Pathways In Food Al...mentioning
confidence: 99%